TRIM27 Negatively Regulates NOD2 by Ubiquitination and Proteasomal Degradation - Zurek, Birte (Public Library of Science, 2012)
NOD2, the nucleotide-binding domain and leucine-rich repeat containing gene family (NLR) member 2 is involved in mediating antimicrobial responses. Dysfunctional NOD2 activity can lead to severe inflammatory disorders, but the regulation of NOD2 is still poorly understood. Recently, proteins of the tripartite motif (TRIM) protein family have emerged as regulators of innate immune responses by acting as E3 ubiquitin ligases. We identified TRIM27 as a new specific binding partner for NOD2. We show that NOD2 physically interacts with TRIM27 via the nucleotide-binding domain, and that NOD2 activation enhances this interaction. Dependent on functional TRIM27, ectopically expressed NOD2 is ubiquitinated with K48-linked ubiquitin chains followed by proteasomal degradation. Accordingly, TRIM27 affects NOD2-mediated pro-inflammatory responses. NOD2 mutations are linked to susceptibility to Crohn's disease. We found that TRIM27 expression is increased in Crohn's disease patients, underscoring a physiological role of TRIM27 in regulating NOD2 signaling. In HeLa cells, TRIM27 is partially localized in the nucleus. We revealed that ectopically expressed NOD2 can shuttle to the nucleus in a Walker A dependent manner, suggesting that NOD2 and TRIM27 might functionally cooperate in the nucleus. We conclude that TRIM27 negatively regulates NOD2-mediated signaling by degradation of NOD2 and suggest that TRIM27 could be a new target for therapeutic intervention in NOD2-associated diseases.